The life within : local Indigenous society in Mexico's Toluca Valley, 1650-1800 - Pizzigoni, Caterina (Stanford University Press, 2012)
This title provides a social and cultural history of the Indigenous people of a region of central Mexico in the later colonial period - as told through documents in Nahuatl and Spanish. It views the Indigenous world from the inside out focusing first on the householders and the greater community.